Representações sociais sobre a moradia e o direito à moradia para técnicos sociais e beneficiários de projetos habitacionais no bairro Santa Maria - Poconé, Claudia Alves (2010)
In areas of subnormal settlement in the Brazilian cities, questions about infrastructure, sanitation and basic services to reflect the social exclusion suffered by your habitants. Santa Maria s district in Aracaju city is an area which receives considerable investments from state government through the buildings, infrastructure and social inclusion actions. This research intends to recognize and to analyze the social description about habitation and beneficiaries warrant habitation and social coach by habitation s projects in Santa Maria s district. This research was developed in two reviews which they were accomplished during one year, and the first was realized two months after beginning the state intervention. The social representation about habitation came to light having many aspects that s includes physical and social s features. The house to the participants is like a refuge they received with cost; although it was emphasized the risky and insalubrity s in the area. The participants report that they never had any access to habitations and now they will go to get it. There was a hope among the participants about the relationships and the new links and social behavior that they associated their personal conduct with their merits in benefit received. Representations about the present, with the current habitations, and the future, which were viewed through all projects, they were showed the continuous process of recreation in the representations with this phenomenon not common.